MECHANICAL CONDITION ASSESSMENT OF TNB IN-SERVICE DISTRIBUTION TRANSFORMERS USING SWEEP FREQUENCY RESPONSE ANALYSIS (SFRA) - Ab Ghani, Sharin; Md Thayoob, Yasmin; Yang Ghazali, Young Zaidey; Sutan Chairul, Imran; Ahmad Khiar, Mohd Shahril (2012)
Distribution transformers in TNB (Tenaga Nasional Berhad) are exposed to the thermal and electrical stresses. Those stresses are effecting to the main mechanical active parts in transformer such as core and winding. In field, lightning strikes and cable faults may cause problem due to transformer core and winding. Sweep Frequency Response Analysis (SFRA) is an off-line diagnostic tool used for finding out any possible winding displacement or mechanical deterioration inside the transformer especially core and winding. SFRA diagnosis is made based on the comparison between two SFRA responses and any significant difference in low, middle and high frequency sub-bands region would potentially indicate mechanical or electrical problem to the winding and core of transformer. The aim of this paper is to assess the condition of TNB in-service distribution transformers by using SFRA method.